Fabricating functionally superior starch based products with fractionated Plantago seed mucilage - Strkalj, Lucija (2025)
Starch plays a crucial role in nutrition and food production, serving as a primary source of energy in diets worldwide. Foods like potatoes, rice, and whole grains represent the base of a meal, serve as carbohydrate source, and contribute to overall health by promoting satiety and aiding digestion. Furthermore, starches are versatile in food production; they serve as thickening agents in cooking and because their behaviour varies widely in nature and they are conducive to further modifications, starches are integral to various processing applications beyond food, including pharmaceuticals and paper manufacturing. Due to its relatively low price, it is easily accessible around the globe, and its importance is studied from a culinary aspect, as well as health and metabolism. Despite its significance, starch consumption brings certain challenges. Firstly, starch and starch-based products are usually overprocessed and lack fibre which is essential for metabolic health. Fibre can reduce blood glucose spikes (a consequence of eating simple carbohydrates and starch), act as prebiotics to maintain gut microbiota, reduce cholesterol and associated risk of cardiovascular illness, and fibre contributes to satiety and healthy eating habits. The addition of fibre and hydrocolloids in starch has long been a subject of research, and improvement of functional properties has been observed by measuring physicochemical and functional properties, such as digestibility (in vitro and in vivo), texture analysis, thermal analysis, microstructure, rheology, pasting properties, and many more. Elucidating mechanisms of interaction between starch and fibre is extremely important as it helps to rationalize their use. Therefore, the aim of this thesis was to explore the addition of novel fibre materials to different types of starch, namely fractionated fibre from seeds of the Plantago genus. The most utilised and commercially relevant Plantago species is Plantago ovata, also known as psyllium. P. ovata is myxospermous plant, meaning that its seeds produce a gel-like coating called mucilage when wet. Importantly, in its dry form, P. ovata mucilage is essentially a layer of dried fibre that can be mechanically separated from the seed. Psyllium husk is often used as a fibre addition to many product categories but its functionality is fairly narrow which has led researchers to explore novel processing methods. Simple fractionations, where the mucilage polysaccharides are extracted with sequential steps usually involving temperature solubilisation and simple separation methods, have gained research interest as they can produce fibres with varying functional properties from the same starting material. Furthermore, the Plantago genus has over 200 species, many of them myxospermous, though underexplored, which prompted us to raise and answer certain research questions. Are there fibre fractions from other Plantago species which are comparable to P. ovata, and can we utilise their gel properties? How would their rheology differ? Would their addition in certain starches change the overall starch profile? Would those changes be transferable to food products? These questions helped shape topics and the flow of this thesis, which is presented in Fig. 1.1.